Psychosocial interventions for adults who were sexually abused as children - Wilen, Jessica S (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: 1. To synthesize the literature on psychosocial interventions for CSA survivors compared to control conditions through pair‐wise meta‐analysis. 2. To assess and compare the effectiveness of different therapeutic interventions in treating adult survivors of child sexual abuse. 3. To determine which interventions are more effective than others in the eligible populations and for specific subgroups of survivors.